Enzymatic hydrolysis of milk proteins: Optimization for obtaining bioactive hydrolysates - Paiva, Virgínia Nardy (2022)
Enzymatic hydrolysis modifies the physical structure of milk proteins and promotes changes in their technological and biofunctional properties. The protein source, the proteolytic enzyme used, and the hydrolysis conditions employed determine the resulting characteristics of the hydrolyzate (eg extent of hydrolysis, peptide profile, and techno- and biofunctional properties). In this sense, the first chapter approaches the main characteristics of the enzymes applied in the hydrolysis of milk proteins (peptidases) and also mentions their applications in the dairy industry, from the use of peptidases in the manufacture of cheese to the hydrolysis of milk proteins for generation of bioactive compounds. Following this theme, the second chapter presents the use of commercial peptidases in the enzymatic hydrolysis of whey proteins aiming for antioxidant hydrolysates released. In this study, the response surface methodology was used to optimize and maximize the hydrolysis degree and antioxidant activity responses. The hydrolysates showed a maximum antioxidant activity of 13.7% by the ABTS methodology, and the highest degree of hydrolysis of 5.16% was obtained by evaluating the soluble peptides in trichloroacetic acid. In general, the objective of this proposal was to present the different strategies for the commercial use of peptidases in dairy technology with a focus on optimizing the hydrolysis conditions of whey proteins to obtain bioactive compounds. Keywords: Commercial enzymes. Enzymatic hydrolysis. Whey protein hydrolysates. Bioactive peptides. Antioxidant activity.